Safety differentiation: emerging competitive edge in drug development. Issue 1 (January 2019) - Uteng, Marianne; Urban, Laszlo; Brees, Dominique; Muller, Patrick Y.; Kullak-Ublick, Gerd A.; Bouchard, Page; Tougas, Gervais; Chibout, Salah-Dine
Highlights: The key value-driver in pharma is break through therapies. Safety is an important integral part of pharmaceutical differentiation. Patient safety is much more than just minimizing side-effects. Integration across all disciplines for safety assessment is key. The stride for best-in-class can boost innovation and quicker development times. Abstract : With increasing expectations to provide evidence of drug efficacy, safety, and cost-effectiveness, best-in-class drugs are a major value driver for the pharmaceutical industry. Superior safety is a key differentiation criterion that could be achieved through better risk:benefit profiles, safety margins, fewer contraindications, and improved patient compliance. To accomplish this, comparative safety assessments using innovative and adaptive nonclinical and clinical outcome-based approaches should be undertaken, and continuous strategic adjustments must be made as the risk:benefit profiles evolve. Key success criteria include scientific expertise and integration between all disciplines during the full extent of the drug development process.